Benzene-1, 3, 5-triyl triformate (TFBen): a convenient, efficient, and non-reacting CO source in carbonylation reactions. Issue 30 (27th July 2016) - Jiang, Li-Bing; Qi, Xinxin; Wu, Xiao-Feng
Graphical abstract: Highlights: Benzene-1, 3, 5-triyl triformate (TFBen) has been prepared for the first time. TFBen has been proven as a kind of convenient and efficient CO source. The synthetic applications of TFBen in carbonylation reactions have been shown. Abstract: Benzene-1, 3, 5-triyl triformate (TFBen) as a kind of convenient and efficient CO source has been prepared for the first time. The character of TFBen as potent and non-reacting CO source has been proven by the successful synthetic applications in carbonylation reactions. Phloroglucinol (1, 3, 5-trihydroxybenzene) is abundant and naturally occurring has been applied as the reusable material for TFBen synthesis.